Pilot study of non‐contrast‐enhanced MRI vs. ultrasound in renal transplant recipients with acquired cystic kidney disease: a prospective intra‐individual comparison. (1st October 2013) - Mühlfeld, Anja S.; Lange, Christian; Kroll, Gisela; Floege, Jürgen; Krombach, Gabriele A.; Kuhl, Christiane; Eitner, Frank; Schrading, Simone
Abstract The incidence of renal cell carcinoma (RCC) after kidney transplantation is 15‐fold increased. Acquired cystic kidney disease (ACKD) is one of the known risk factors. We performed a small pilot study to assess the role of non‐enhanced magnetic resonance imaging (MRI) as a tool for intensified screening in renal transplant recipients with ACKD. Renal ultrasound was used to assess the native kidneys of 215 renal transplant recipients. Thirty patients with 54 kidneys, fulfilling the criteria of ACKD, underwent non‐enhanced MRI at 1.5T using T2‐ and T1‐weighed as well as diffusion‐weighted sequences with a high spatial resolution. Among the 54 kidneys assessed by both methods, three RCCs were identified (6%). Of those, one RCC was detected by both imaging methods (33%), while two RCCs were diagnosed by MRI alone (67%). MRI identified an additional four proteinaceous or hemorrhagic cysts that did not fulfill the criteria for RCC but were classified as suspicious. All of these lesions were stable in size and appearance in follow‐up studies. In conclusion, non‐enhanced MRI was more sensitive than ultrasound in identifying RCCs and lesions suspicious for RCC and thus appears to be a useful secondary screening tool in patients with ACKD after renal transplantation.